Naming of pictures by LIS and MBB students - Geslani, Kathleen B.; Punzalan, Ricardo L. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2003)
Humans, over the years of their existence, have acquired knowledge on a lot of things and in a lot of ways. Concepts of things and events are instilled in the mind and a new discovery would only bring wonder. But upon closer inspection and familiarization, things become clear to them, as memory search for anything similar to it begins. Categorization takes place. Validation of the similarity or likeness of the 'new thing', can be inferred as an example of something already known of.
Naming pictures is the concern of this study. Twenty-one pictures were named by two groups of students, seven Library and Information Science (LIS) and seven Molecular Biology and Biotechnology (MBB) undergraduate students.
Respondents were selected using the following criteria: 1) age limit includes from 18 to 21 years of age; 2) college students and are enrolled for second semester of academic year 2002-2003; 3) original LIS students with student number 2001 [major LIS subjects taken should be at least 12 units including the subject LIS 61 (Cataloging and Classification 1)]; and 4) original students of the MBB with student number 2000 [major MBB subjects taken should be at least 18 units, with no specific subject requirement]. The pictures were selected from a wide variety of books, internet and advertisements. Set 1 pictures were MBB-related pictures; set 2 were pictures of common/generic objects; and set 3 pictures were LIS-related. The names given by the students were corrected and compared to the actual name of the object in the picture. This would show how well the two groups named a picture in their respective subject fields.
LIS students scored higher in the set of pictures where the objects named leaned on the subject field. While the MBB students scored higher in the set of pictures where the objects named leaned on their subject field. Furthermore, in the set of pictures considered common objects, an insignificant difference was seen in their test scores. Thus, the LIS and MBB student differed in naming pictures. The exposure to an individual's subject field appeared to have influenced the way they named pictures.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines -- Students; Picture interpretation